Green Conversion of N‐Acetylglucosamine into Valuable Platform Compound 3‐Acetamido‐5‐acetylfuran Using Ethanolamine Ionic Liquids as Recyclable Catalyst. Issue 16 (23rd April 2021) - Zang, Hongjun; Li, Huanxin; Jiao, Shuolei; Lou, Jing; Du, Yannan; Huang, Nalan
Abstract: N ‐acetylglucosamine (NAG) is the monomer of chitin which is the most abundant nitrogen‐containing biomass. Thus, NAG is a potential nitrogen‐rich feedstock for the production of renewable organonitrogen chemicals. In this work, ethanolamine ionic liquids were synthesized easily from inexpensive raw materials and subsequently used as catalysts for NAG conversion to produce 3‐acetamido‐5‐acetylfuran (3A5AF). Using triethanolamine hydrochloride ([TEA]Cl) ionic liquid as the catalyst, a high 3A5AF yield of 62.0 % was obtained at the optimum reaction conditions of 170 °C and 20 min. Moreover, this ionic liquid exhibited good reusability and still had good catalytic activity after recycling five times. High‐performance liquid chromatography‐mass spectrometry (HPLC‐MS) analysis provided the relevant basis for rationalizing the reaction mechanism. Therefore, our study presents an intriguing and sustainable protocol for the direct conversion of NAG. Abstract : In this paper, a series of ethanolamine ionic liquids were synthesized through a one‐step protonation reaction and used as catalysts for the conversion of NAG to 3A5AF. Among them, triethanolamine hydrochloride ionic liquid exhibited good catalytic activity and provided 35AF in 62.0 % yield at 170 °C within 20 min. The ionic liquid exhibited good reusability.